The Effect of Price and Product Quality on Consumer Satisfaction of Goat Milk - Zahara, Rita (Green Publisher, 2024)
The purpose of this study was to determine and analyze: (1) Price; (2) Product quality; (3) Consumer Satisfaction; (4) Price Effect on Consumer Satisfaction; (5) Effect of Product Quality on Consumer Satisfaction; and (6) Effect of Price and Product Quality on Consumer Satisfaction of Goat Milk at Company both simultaneously and partially. The research method used in this research is Descriptive and Verification, the unit of analysis in this study is the consumers of Goat milk Company in Bandung Regency and surrounding areas with a sample of 100 people. The analysis used in this research is Path Analysis with the help of the SPSS for Windows 22.0 program. Based on the results of the study, it was found that: (1) The price at Company is good (2) Product Quality at Company good (3) Consumer Satisfaction at Company is quite good (4) Price affects Consumer Satisfaction at Company (5) Product Quality affects Consumer Satisfaction at Company (6) Price and Product Quality have a joint effect on Consumer Satisfaction at Company. The results showed that price and product quality proved to have an effect on consumer satisfaction of Etawa peranakan goat milk at Company both partially and simultaneously, but when viewed partially, it turns out that product quality is the more dominant influence.